Politeness Strategies Of Request Found In Pride And Prejudice Movie - Hastari, Asri Dwi, Prof. Dr. Endang Fauziati, M.Hum, Drs. Agus Wijayanto, MA, Ph.D (2013)
This study focuses on politeness strategy of request found in Pride and Prejudice movie using Brown and Levinson‟s theory. Someone should know how to utter a polite request in English, because a request can threat both of the speaker and hearer‟s face. Speakers have to minimize the imposition in their request. Therefore, the users of the language must give attention to the use of politeness strategy especially in delivering request so that it can minimize the potential of face loss. The purpose in using politeness strategy is to make people can communicate in the right language based on the context when the communication is occurred. This research aims to investigate the following questions: (1) the types of politeness strategies of request are used in Pride and Prejudice movie, (2) the dominant types of politeness strategies of request are used in Pride and Prejudice movie, and (3) the factors contribute to the choice of politeness strategies in realizing request in Pride and Prejudice movie. This research is a descriptive qualitative research. The data of this research are the excerpts which contain politeness strategy of request utterances taken from the conversation of the characters in Pride and Prejudice movie. The collected data are analyzed by using Brown and Levinson‟s theory of politeness strategy. Then, the data are determined its type of politeness strategy based on the theory. Finally the dominant type of politeness strategy of request and the factors influencing it is determined. The last, conclusion is drawn. The result of the study those are, 1) there are four types of politeness strategies of request which are used by the characters of Pride and Prejudice movie, those four strategies are Bald on Record, Positive Politeness, Negative Politeness and Off Record, 2) the greatest amount of politeness strategy of request which is used in Pride and Prejudice movie is Bald on Record that is 45 excerpts or 61.64%, the second is Positive Politeness which is found in 8 excerpts or 10.96%, the others are Negative Politeness is found in 16 excerpts or 21.92%, and Off Record is found in 4 excerpts or 5.48%, thus, the dominant type of politeness strategy of request in Pride and Prejudice movie is Bald on Record, 3) furthermore, the result shows that the characters in Pride and Prejudice movie were influenced by two factors in realizing politeness strategy of request, those factors are payoff and relevant circumstances cover "social distance‟ (D) of speaker and hearer, relative "power‟ (P) of speaker and hearer, and the absolute ranking (R) of imposition in the particular culture.